Fat patterning differences in male and female persons: Application of a highly accurate and precise ultrasound technique - Störchle, P.; Sengeis, M.; Müller, W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Body composition influences both health and physical performance. Particularly in weight-sensitive sports, underweight and body composition disturbances can cause serious medical problems and can lead to severe performance setbacks [1]. For investigating body fat and subcutaneous adipose tissue (SAT) patterning in athletes, highly accurate and precise measurement methods should be applied. Diagnostic ultrasound (US) fulfills these criteria and also enables measurements in the field. The aim of this study was to examine the sex specific fat distribution differences at eight standardised sites used in this novel US method. Methods: Measurements were carried out according to the standardised measurement protocol of W. Müller et al., 2016 [2]. The used sites in this protocol were: upper abdomen (UA), lower abdomen (LA), erector spinae (ES), distal triceps (DT), brachioradialis (BR), lateral thigh (LT), front thigh (FT) and medial calf (MC). 24 subjects (12 males and 12 females) were examined. In order to cover a wide range of SAT thicknesses the BMI ranged from 18.6 to over 40 kgm-2. For evaluating the US images, a semi-automatic tissue contour detection and measurement algorithm was used (FAT software, rotosport.com). Results: The five sites UA, LA, LT, FT, and MC showed significant differences between men and women in this group (p < 0.05), whereas ES, DT, and BR did not. In men, UA and LA contributed 51% to the sum of the eight fat thicknesses, whereas in women it was only 34%. In women, all three sites on the leg: LT, FT and MC (women: 26%, 12% and 8%; men: 15%, 8% and 5%, respectively) showed significantly higher SAT values. Mean value of the total sum of SAT was 85 mm in the men`s group (mean BMI 26.8 kgm-2) and 117 mm in the women`s group (mean BMI 24.6 kgm-2). Discussion: The results obtained in this group show the pronounced SAT thickness differences at the eight sites chosen for the standardised fat patterning analysis in individuals and between a group of men and a group of women. LT, a site that has not been used in preceding studies, was found to be a fat depot site which is more pronounced in women than in men. In further studies, the differences between males and females should be in investigated in larger groups. This measurement technique can also be applied for SAT studies in various groups of athletes and also in overweight persons. This method [2] provides a sensitivity for fat patterning studies not reached by any other method before.